Future data and security engineering : 4th International Conference, FDSE 2017, Ho Chi Minh City, Vietnam, November 29-December 1, 2017, Proceedings /: 4th International Conference, FDSE 2017, Ho Chi Minh City, Vietnam, November 29-December 1, 2017, Proceedings. (2017) - Unknown
No abstract available